Myocardial rupture and systemic lupus erythematosus: a case report. Issue 1 (30th December 2020) - Neto, Ana; Torres, Sofia; Pissarra, Diana; Vasconcelos, Gisela
Abstract: Background: Systemic erythematous lupus (SLE) is an autoimmune disease associated with significant cardiovascular morbidity and mortality, even in young patients. Case summary: A young female with recently diagnosed SLE under corticotherapy developed pulmonary oedema and respiratory failure. The diagnostic workup revealed mildly elevated cardiac troponin, significantly elevated NT-proB-type natriuretic peptide (NT-proBNP) and mild pericardial effusion without other echocardiographic abnormalities. Systemic erythematous lupus-associated myocarditis was presumed, and her clinical status improved after corticotherapy intensification. However, transthoracic echocardiogram repeated days later revealed a large pericardial effusion with findings suggestive of a contained myocardial rupture originating in the inferolateral basal left ventricular (LV) segment, which was confirmed by computed tomography scan. Cardiac catheterization exhibited normal coronary arteries. The patient was submitted to cardiac surgery and the LV pseudoaneurysm was successfully repaired. Discussion: Myocardial rupture with LV pseudoaneurysm formation usually occurs in the setting of acute myocardial infarction, but also in other rare contexts. Cardiac rupture is associated with an extremely high mortality unless early diagnosis and urgent surgical intervention are provided.